Inovasi dan Diversifikasi Produk Gerabah sebagai Katalisator Pertumbuhan Laba pada UMKM Sektor Kerajinan - Nengsih, Rita; Samsul; Mukhdasir, Mukhdasir; Khairuna, Khairuna; Ahyar, Muhammad (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study explores the strategic significance of innovation and product diversification in enhancing profit growth for MSMEs in the pottery craft sector in Indonesia. The research employs a literature review approach, with a focus on the adaptation of contemporary designs, the use of material combinations, and the expansion of product functions. These strategies enable MSME actors to reach broader market segments, increase selling prices, and create significant economic value. The study indicates a direct correlation between innovation and key financial indicators, including return on investment (ROI), net profit margin, and sales volume. Moreover, the diversification of products has been shown to enhance business resilience in the face of market fluctuations, thereby generating opportunities in the domains of decoration, tourism, and sustainable lifestyles. This study underscores the significance of a collaborative ecosystem comprising designers, government entities, and digital platforms to systematically support the innovation process. The adoption of an integrated innovation approach by pottery MSMEs has the potential to catalyze their transformation into a creative sector that is characterized by competitiveness, adaptability, and sustainability.